The Impact of Affective Context on Autobiographical Recollection in Depression. (May 2018) - Hitchcock, Caitlin; Golden, Ann-Marie J.; Werner-Seidler, Aliza; Kuyken, Willem; Dalgleish, Tim
Across two studies we investigated the influence of contextual cues on autobiographical memory recall. In Study 1, participants ( N = 37) with major depressive disorder, in episode or in varying degrees of remission, were administered a Negative Autobiographical Memory Task (NAMT) that required them to retrieve negatively valenced memories in response to positive cue words (a positive context). We reasoned that increased depression symptom severity would be associated with a reduced ability to override priming from this disadvantageous context. Consequently, we hypothesized that increased depressive severity would counterintuitively be associated with reduced negativity ratings for retrieved personal memories to positive cues on the NAMT. This hypothesis was supported. Study 2, using a community sample ( N = 63), demonstrated that a similar reduction in memory negativity was observed in individuals with lower working memory capacity—an index of executive control. Implications for autobiographical memory and executive training paradigms for depression are discussed.